Marrow Fat and Bone—New Perspectives - Fazeli, Pouneh K. (Endocrine Society, 2013)
CONTEXT: There is growing interest in the relationship between bone mineral density, bone strength, and fat depots. Marrow adipose tissue, a well-established component of the marrow environment, is metabolically distinct from peripheral fat depots, but its functional significance is unknown. OBJECTIVE: In this review, we discuss animal and human data linking the marrow adipose tissue depot to parameters of bone density and integrity as well as the potential significance of marrow adipose tissue in metabolic diseases associated with bone loss, including type 1 diabetes mellitus and anorexia nervosa. Potential hormonal determinants of marrow adipose tissue are also discussed. CONCLUSIONS: We conclude that whereas most animal and human data demonstrate an inverse association between marrow adipose tissue and measures of bone density and strength, understanding the functional significance of marrow adipose tissue and its hormonal determinants will be critical to better understanding its role in skeletal integrity and the role of marrow adipose tissue in the pathophysiology of bone loss.